Modelling West Nile Virus and Usutu Virus Pathogenicity in Human Neural Stem Cells - Silvia Riccetti; Alessandro Sinigaglia; Giovanna Desole; Norbert Nowotny; Marta Trevisan; Luisa Barzon (Viruses, 2020)
West Nile virus (WNV) and Usutu virus (USUV) are genetically related neurotropic mosquito-borne flaviviruses, which frequently co-circulate in nature. Despite USUV seeming to be less pathogenic for humans than WNV, the clinical manifestations induced by these two viruses often overlap and may evolve to produce severe neurological complications. The aim of this study was to investigate the effects of WNV and USUV infection on human induced pluripotent stem cell-derived neural stem cells (hNSCs), as a model of the neural progenitor cells in the developing fetal brain and in adult brain. Zika virus (ZIKV), a flavivirus with known tropism for NSCs, was used as the positive control. Infection of hNSCs and viral production, effects on cell viability, apoptosis, and innate antiviral responses were compared among viruses. WNV displayed the highest replication efficiency and cytopathic effects in hNSCs, followed by USUV and then ZIKV. In these cells, both WNV and USUV induced the overexpression of innate antiviral response genes at significantly higher levels than ZIKV. Expression of interferon type I, interleukin-1β and caspase-3 was significantly more elevated in WNV- than USUV-infected hNSCs, in agreement with the higher neuropathogenicity of WNV and the ability to inhibit the interferon response pathway.